Influence of Catechol-O-methyltransferase on Executive Functioning Longitudinally After Early Childhood Traumatic Brain Injury: Preliminary Findings. Issue 3 (May 2016) - Kurowski, Brad G.; Backeljauw, Barynia; Zang, Huaiyu; Zhang, Nanhua; Martin, Lisa J.; Pilipenko, Valentina; Yeates, Keith; Taylor, H. Gerry; Wade, Shari
Abstract : Objective: To elucidate the association of a functional catechol- O -methyltransferase (COMT) genotype (rs4680) with recovery of executive functions up to 18 months after early childhood traumatic brain injury (TBI) compared with an orthopedic injury (OI) group. Setting: Outpatient. Participants: A total of 134 children with a moderate to severe TBI ( n = 63) or OI ( n = 71) between the ages of 3 and 6 years who were followed 18 months postinjury. Design: Case-comparison, longitudinal cohort Main Measures: The Behavior Rating Inventory of Executive Function, developmental NEuroPSYchological Assessment (NEPSY) of Verbal Fluency, and a modified Stroop Test for young children (Shape School). Results: The low-activity COMT enzyme genotype (AA) was associated with better scores on the developmental NEPSY of Verbal Fluency ( F = 3.80; P = .02) and the Shape School ( F = 2.89; P = .06) in all participants when controlling for injury type (TBI vs OI) over the first 18 months after injury. Injury type (TBI vs OI) did not significantly moderate the effect of the COMT genotypes on executive function recovery. Conclusion: This study provides preliminary evidence for a role of COMT genotypes in long-term recovery of executive function after pediatric TBI and OI. Larger studies are needed to determine the exact link between genetic variation in the COMT gene and TBI recovery in children.